2007
DOI: 10.1080/00914030701215701
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Morphology of Nitrile Rubber Toughened Polystyrene

Abstract: Mechanical properties and morphology of blends of polystyrene and finely powdered (uncrosslinked and crosslinked) nitrile rubber were studied with special reference to the effect of blend ratio. Blends were prepared by melt mixing polystyrene and nitrile rubber in an internal mixer at 180 C in the composition range of 0-20 wt% nitrile rubber. The tensile stress=strain properties and impact strength of the polystyrene=nitrile rubber blends were determined using injection molded test specimens. In comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…PECA-2.5 demonstrated much better elastic properties than PECA-5 and this could be due to the increased number of rubbery domains in PECA-5 with more interfacial adhesion failure sites that can cause elongation failure. This is also observed in rubber-modified rigid polymers and studies indicate that proper modification of interfacial adhesion diminishes early breaks during elongation [ 36 ]. Adding caffeic acid to PECA-2.5 (PECA2.5-1) did not affect the elastic modulus of the blend but elongation was reduced to about 10%, instead.…”
Section: Resultsmentioning
confidence: 70%
“…PECA-2.5 demonstrated much better elastic properties than PECA-5 and this could be due to the increased number of rubbery domains in PECA-5 with more interfacial adhesion failure sites that can cause elongation failure. This is also observed in rubber-modified rigid polymers and studies indicate that proper modification of interfacial adhesion diminishes early breaks during elongation [ 36 ]. Adding caffeic acid to PECA-2.5 (PECA2.5-1) did not affect the elastic modulus of the blend but elongation was reduced to about 10%, instead.…”
Section: Resultsmentioning
confidence: 70%
“…We observed that enhancement in impact strength versus rubber content has an optimum value. This was further confirmed in a research by Kurian and his coworker who investigated on the toughening behavior of PS/nitrile rubber blends . They found an optimum amount of 10% for nitrile rubber incorporation into PS matrix.…”
Section: Resultsmentioning
confidence: 72%
“…superior breaking stress of PS (50 MPa) compared with PS/rubber10 blends(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) reflected the brittleness of the polymer, which did not reach its yield point under the testing conditions used here.The elongation at break of the studied blends progressively increased, while elastic Young's modulus monotonically decreased. To distinguish the curves of the blends, the highest amount of yield stress and extension is seen for PS/COPOLY sample.…”
mentioning
confidence: 86%
“…Consequently, rubber toughening is often used to overcome the brittleness of glassy polymers such as polystyrene (PS). Polystyrene has been toughened by blending with rubbers such as styrene-butadiene (SBR) [3], natural rubber (NR) [4], polybutadiene (BR) [5], ethylene-propylene-diene terpolymer (EPDM) [6] and nitrile rubber (NBR) [7]. A major improvement in toughness is obtained when the rubber particles are small (1)(2)(3)(4) …”
Section: Introductionmentioning
confidence: 99%